THE INTEGRATION OF ISLAMIC VALUES IN THE DEVELOPMENT OF LISTENING COURSE MATERIALS - Mazroatul Ishlahiyah; Mira Shartika (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2020)
Despite the fact that material development has been widely discussed and reported in the area of English Language Teaching, there is not much empirical evidence available so far that addresses material development in listening, especially in Indonesian context. To fill this gap, the writers examined the result of material development that includes the integration of Islamic values in some units of Nunan’s Listen in 1 book. Employing Dick, Carey, & Carey model of Research and Development design, the article exhibits the integration of Islamic values in the activities of warming up, main, and reflective, and game. The result of the study requires further research on material development, particularly on the creation of further material and audio developments.